Procedural framework of the resources cost effective use of cutting works technologies. Issue 1 (March 2020) - Mushkarova, O; Mikheeva, M; Chepic, F; Vasiliev, S
Abstract: With a variety of technologies for the cutting works, the choice of them should be determined by a combination of various factors that allow us to estimate the possible level of resource savings at each stage of such work. At the moment, the ecological effect extended for a certain period of time cannot be calculated precisely. It must be taken into account when evaluating the economic effect of resource savings at the enterprises of the timber complex. Using the structural-logical diagram of methodological approaches in order to establish factors and indicators of the resource-saving effect, a system analysis is carried out, which allows us to draw up an algorithm for generating an estimate of the resource-saving effect of various cutting works.